Durable Leukemic Remission and Autologous Marrow Recovery with Random Chromosomal Abnormalities after Allogeneic Hematopoietic Stem Cell Transplantation for Chronic Lymphocytic Leukemia. (3rd January 2019) - Nishikii, Hidekazu; Kurita, Naoki; Shinagawa, Atsushi; Sakamoto, Tatsuhiro; Kusakabe, Manabu; Yokoyama, Yasuhisa; Kato, Takayasu; Sakata-Yanagimoto, Mamiko; Obara, Naoshi; Hasegawa, Yuichi; Nakamura, Naoya; Chiba, Shigeru
Abstract : A 38-year-old woman with aggressive clinical course of chronic lymphocytic leukemia (CLL) was treated with 8 courses of R-CHOP. Clinical remission was achieved, while B-cell clonality remained. Allogeneic hematopoietic stem cell transplantation was performed with reduced intensity conditioning (fludarabine and 2-Gy total body irradiation). However, autologous hematopoietic recovery occurred within a month after the transplant. Nevertheless, B-cell clonality became undetectable at 14 days after transplant, which has been kept so for over 10 years with clinical remission. Cytogenetic analyses were repeatedly performed and demonstrated nonclonal chromosomal aberrations, although the patient did not develop any secondary malignancies. One possible explanation for the clinical course is a very short-term allogeneic immune reaction helping eradication of residual CLL cells.